Aku Kesepian: Pemaknaan Remaja Yatim Piatu terhadap Perubahan Dinamika Keberfungsian Keluarga - Nafisah, Rofa Hasna; Hanami, Yuliana (Universitas Muhammadiyah Metro, 2024)
The family is the most miniature society system bound to change. Changes in the family structure, such as the loss of a family member, can never be predicted. In adolescents, family is the primary source of support in fulfilling developmental tasks and ensuring their well-being. Adolescents who experience changes in family structure, especially adolescents whose parents have died, become vulnerable to various kinds of problems. In this study, an analysis was carried out regarding how adolescents interpret the function of their family after the parental loss. This research was conducted using a qualitative method through a phenomenological approach. Data was collected through image assessment and semi-structured interviews, which were analyzed using interpinterpretive phenomenological analysis techniques. The data processing results show three superordinate themes from the subject's meaning related to her family function, which include family identity, parenting style, and